Study of heterogeneity in immune responses to exposure in breast cancer: A protocol for a systematic review - Amene Saghazadeh (PLoS ONE, 2025)
Background Radiation is a treatment modality of interest in both palliative and curative settings for patients with breast cancer (BC). Despite many advances in radiation oncology, anti-radiation resistance remains a problem in mechanistic aspects. Studies show that immune cells respond to radiation in a heterogeneous manner and suggest the determinant role of these responses in the ultimate clinical classification of patients with BC as anti-radiation resistant/sensitive. Objective A systematic review of in vivo and in vitro studies will be defined here to assess the radiation response of immune cells in BC comprehensively. Methods/design A systematic search for in vivo and in vitro studies will collect studies that compare the radiation alone-treated and control (untreated or sham) subjects, as well as subjects treated with radiation in combination and subjects treated with radiation alone. The primary outcome of interest will be measures of the abundance of immune cell subsets. The secondary outcomes will include measures derived from co-culture assays leading to immunoregulatory roles or mechanisms proposed for the potential cross-talks between immune-BC cells that will be influenced by radiation. The review results will be primarily synthesized in a narrative and qualitative manner. Meta-analysis will be considered if there are three or more observations with data available for a specific outcome. We will use the SYRCLE “Risk of Bias” assessment tool for appraising the risk of bias in preclinical in vivo studies, and given the lack of standardized instruments for in vitro studies, we will design a checklist suitable for our specific in vitro research questions and publish it along with our systematic review.